ANALYZING CINEMA DISCOURSE: TELECINEMATIC DISCOURSE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This annotation aims to highlight key points and provide additional context for the analysis of cinema discourse by recognizing the importance of understanding a film's context is paramount for a nuanced analysis. It considers the specific historical events, social movements, and political climate surrounding the film's creation and examine how the film's context informs its themes, characters, and narrative choices.  It encourages a deeper understanding of the art form and its impact on society, culture, and the human experience.